Unveiling Spatial Politics in Indonesia: The Eigendom Verponding Number 1278 Land Dispute Involving Pertamina in Surabaya City - Dimas Septo Nugroho; Glady Oralyanto Nur Rizki; Sokhib , Najmah Rindu Aisy; Mohammad Niamulloh (Universitas Brawijaya, 2026)
This study examines the Pertamina land dispute in Darmo Hill, Surabaya, through the theoretical frameworks of Production of Space (Lefebvre) and Spaces of Capital (Harvey). Employing qualitative content analysis of 2025 headline news articles and agrarian regulation, the study underscores the conflict between state capital interests and citizens’ rights. The results indicate that the state and state-owned enterprises function as collective capital actors, reproducing space via administrative control and converting the use value of housing into the exchange value of assets. The study identifies regulatory ambiguity not as a passive legal byproduct, but as an intentional spatial strategy to sustain capital accumulation in established urban areas. It recommends establishing a participatory and transparent state asset verification mechanism to prevent unilateral claims by state-owned enterprises that undermine legal certainty and substantive justice.